Seoul G20 Summit : will it adopt Singapore’s 3G ideas? - Rana, Pradumna B. (2011)
The invitation to Singapore to participate in the G20 Summit is a recognition that the Global Governance Group (3G) it initiated can contribute to the G20 process. In Seoul, the leaders should adopt the 3G ideas to position the G20 Summit as the universal and unquestioned premier fora for overseeing global economic governance.